Step-by-step total laparoscopic hysterectomy - Chatterjee, Abhinibesh; Dutta, Annesha; Chatterjee, Polly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Total laparoscopic hysterectomy (TLH) is the complete hysterectomy including transection of the uterine vessels and opening/closure of the vaginal vault performed laparoscopically. This procedure can be performed as an alternative to total abdominal hysterectomy in many cases. In this short communication, we would like to share our experience of 1000 cases of total hysterectomy done laparoscopically witbout having caused any intraoperative or post operative complications.